Personal Income Tax Progressivity : Trends and Implications - Gerber, Claudia (IMF Working Papers; Working Paper, 2018)
This paper discusses how the structure of the tax system affects its progressivity. It suggests a measure of progressive capacity of tax systems, based on the Kakwani index, but independent of pre-tax income distributions. Using this and other progressivity measures, the paper (i) documents a decline in progressivity over the last decades and (ii) examines the relationship between progressivity and economic growth. Regressions do not reveal a significant impact of progressivity on growth, suggesting that efficiency costs of progressivity may be small-at least for degrees of progressivity observed in the sample.